Effectiveness of a pragmatic school‐based universal intervention targeting student resilience protective factors in reducing mental health problems in adolescents. (3rd April 2017) - Dray, Julia; Bowman, Jenny; Campbell, Elizabeth; Freund, Megan; Hodder, Rebecca; Wolfenden, Luke; Richards, Jody; Leane, Catherine; Green, Sue; Lecathelinais, Christophe; Oldmeadow, Christopher; Attia, John; et al.
ABSTRACT: Worldwide, 10–20% of adolescents experience mental health problems. Strategies aimed at strengthening resilience protective factors provide a potential approach for reducing mental health problems in adolescents. This study evaluated the effectiveness of a universal, school‐based intervention targeting resilience protective factors in reducing mental health problems in adolescents. A cluster randomised controlled trial was conducted in 20 intervention and 12 control secondary schools located in socio‐economically disadvantaged areas of NSW, Australia. Data were collected from 3115 students at baseline (Grade 7, 2011), of whom 2149 provided data at follow up (Grade 10, 2014; enrolments in Grades 7 to 10 typically aged 12–16 years; 50% male; 69.0% retention). There were no significant differences between groups at follow‐up for three mental health outcomes: total SDQ, internalising problems, and prosocial behaviour. A small statistically significant difference in favour of the control group was found for externalising problems. Findings highlight the continued difficulties in developing effective, school‐based prevention programs for mental health problems in adolescents. Trial registration: ANZCTR (Ref no: ACTRN12611000606987).